2021
DOI: 10.26603/001c.21419
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Cutting Alignment Scoring Tool (CAST) to Assess Trunk and Limb Alignment During a 45-Degree Side-Step Cut

Abstract: Background Three-dimensional (3D) motion analysis is considered the gold standard for evaluating human movement. However, its clinical utility is limited due to cost, operating expertise, and lengthy data processing time. Numerous qualitative scoring systems have been introduced to assess trunk and lower extremity biomechanics during functional tasks. However, the reliability of qualitative scoring systems to evaluate cutting movements is understudied. Purpose/Hypotheses: To assess the inter-rater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
0
12
0
2
Order By: Relevance
“…27 In a another study by Weir et al, an unplanned 45-degree side step cut was assessed in 15 junior (age 15.1 + 1.2 years) and 15 elite senior (age 22.1+ 2.3 years) female field hockey players utilizing 2-D video based measurements of whole body kinematics. 26 Weir et al found excellent intra-rater reliability (ICC: 0.99-1.00) for angular measurements including dynamic knee valgus angle, trunk lateral flexion angle, knee flexion angle, thigh abduction angle and trunk flexion angle, and poor to good reliability (ICC: 0.38-0.54) for displacement based measurements including foot placement and dynamic medial knee shift. 26 Weir et al found good to excellent inter-rater reliability (ICC: 0.66-0.97) for all angular measurements and poor to excellent inter-rater reliability (ICC: 0.22-0.87) for displacement based measurements.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…27 In a another study by Weir et al, an unplanned 45-degree side step cut was assessed in 15 junior (age 15.1 + 1.2 years) and 15 elite senior (age 22.1+ 2.3 years) female field hockey players utilizing 2-D video based measurements of whole body kinematics. 26 Weir et al found excellent intra-rater reliability (ICC: 0.99-1.00) for angular measurements including dynamic knee valgus angle, trunk lateral flexion angle, knee flexion angle, thigh abduction angle and trunk flexion angle, and poor to good reliability (ICC: 0.38-0.54) for displacement based measurements including foot placement and dynamic medial knee shift. 26 Weir et al found good to excellent inter-rater reliability (ICC: 0.66-0.97) for all angular measurements and poor to excellent inter-rater reliability (ICC: 0.22-0.87) for displacement based measurements.…”
Section: Discussionmentioning
confidence: 99%
“…26 Weir et al found excellent intra-rater reliability (ICC: 0.99-1.00) for angular measurements including dynamic knee valgus angle, trunk lateral flexion angle, knee flexion angle, thigh abduction angle and trunk flexion angle, and poor to good reliability (ICC: 0.38-0.54) for displacement based measurements including foot placement and dynamic medial knee shift. 26 Weir et al found good to excellent inter-rater reliability (ICC: 0.66-0.97) for all angular measurements and poor to excellent inter-rater reliability (ICC: 0.22-0.87) for displacement based measurements. 26 Again, several differences in study design need to be discussed between the work of Weir et al and this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations